Dietary RNA from Torula Yeast Prevents Capillary Regression in Atrophied Skeletal Muscle in Rats - Hao Lin; Jihao Xing; Xiaoqi Ma; Ryosuke Nakanishi; Hiroyo Kondo; Mica Fujita; Keita Sutoh; Noriaki Maeshige; Hidemi Fujino (Life)
Chronic neuromuscular inactivity induces capillary regression within skeletal muscle. The objective of this study was to investigate the potential effects of dietary nucleic acids in counteracting the capillary reduction linked to chronic neuromuscular inactivity in the soleus muscle. The study utilized four distinct groups of female Wistar rats: a control group (CON), a hindlimb-unloading group (HU), an HU group supplemented with DNA (HU + DNA), and an HU group supplemented with RNA (HU + RNA). For a duration of two weeks, rats in the HU + DNA and HU + RNA groups were administered 1500 mg/kg of DNA or RNA orally on a daily basis. Two weeks of hindlimb unloading was concomitant with a reduction in the absolute weight of the soleus muscle and the capillary-to-fiber (C/F) ratio. This was associated with changes due to disuse, including increased accumulation of reactive oxygen species (ROS) and reduced levels of superoxide dismutase (SOD-2), along with elevated levels of thrombospondin-1 (TSP-1), an anti-angiogenic factor. Administering DNA at a medium concentration in the diet did not effectively prevent the reduction in the ratio between capillaries and fibers. In contrast, the equivalent concentration of RNA successfully averted the regression of capillaries during the unloading phase. Additionally, reactive oxygen species (ROS), superoxide dismutase-2 (SOD-2), and thrombospondin-1 (TSP-1) protein were kept at the same levels as in the control. The aforementioned findings reveal that RNA is more effective than DNA in preventing capillary regression triggered by muscle atrophy.